Implementation of ICT-Based Learning Media in PAI Subjects at SMK N 5 Padang (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
This research explores the application of Information and Communication Technology (ICT) in developing Islamic Religious Education (PAI) learning media. This research aims to provide a flexible and engaging learning experience for students while aligning it with the principles of Islamic education. This research uses qualitative research methods with field research type. Researchers used data collection methods, namely observation, interviews and documentation. Data sources were taken using purposive sampling techniques with informants namely school principals and teachers. Data analysis techniques use data reduction, data presentation, and data verification. This research advocates for strategic planning and investment in ICT infrastructure, along with ongoing professional development for teachers to ensure the successful integration of technology in PAI classrooms. In conclusion, the implementation of ICT-based learning media in the context of Islamic education shows promising potential for improving the quality of PAI teaching. This research provides valuable insights and recommendations for educators and policymakers who wish to utilise technology to improve the overall effectiveness of Islamic education.
Keywords: Implementation; ICT-based learning media; PAI learning